Allergic Contact Dermatitis (type IV hypersensitivity) and type I hypersensitivity following aromatherapy with ayurvedic oils (Dhanwantharam thailam, Eladi coconut oil) presenting as generalized erythema and pruritus with flexural eczema - Chembolli Lakshmi (Wolters Kluwer Medknow Publications, 2014)
Herbal and Ayurvedic medications, believed to be "mild" and "natural" are usually sought as the first line of treatment before resorting to "stronger" allopathic medication. There are very few reports of adverse reactions to either topical and/or systemic Ayurvedic medications. Massage aromatherapy with ayurvedic oils plays an important role in alleviation of pain, but may cause allergic contact dermatitis. This is the second case report of allergic contact dermatitis to ayurvedic oil.